تأثير الزواج المبكر على التحصيل الدراسي للأبناء في منطقتي الحوامدية والبدراشين: دراسة سوسيوانثروبولوجية ميدانية - كامل، علياء الحسين محمد (جامعة عين شمس - كلية الآداب, 2017)
يعتبر الزواج المبكر ظاهرة منتشرة في الريف المصري بوجه خاص، فهو يعتبر أحد الموروثات التراث الثقافي للمجتمعات الريفية وأنه من الظواهر التي قد يكتب لها الاستمرار والبقاء لفترة تاريخية مقبلة لاسيما في المناطق الريفية وذلك نتيجة لعدم اهتمام الأسرة بسببها تزويج الإناث في سن مبكرة، وأن من عادات الزواج المبكر تؤثر سلبا على المجتمع ككل وخصوصا الشباب في مقتبل عمرهم لأنه يعوق استكمالهم للعملية التعليمية ومن ثم يعرقل وضعهم الاجتماعي والاقتصادي والصحي وخاصة للسيدات لما يتعرضن له من ضغوط نفسية وفسيولوجية في تلك المرحلة العمرية المبكرة.
Early marriages widespread phenomenon in the Egyptian countryside in particular, Fehr is one of the legacies of the cultural heritage of rural communities and that of phenomena that might write it to continue and remain a historic time to come, especially in rural areas and due to the lack of interest in family education and the weakness of social awareness or as a result poor economic conditions that forced the family because of marrying off girls at an early age, And that of early marriage habits negatively affect the whole of society, especially young people in the prime of their age because it hampers their completion of the educational process and therefore hinders their social status, economic and health, especially women because they suffer from psychological stress and physiological at that early age.
Keywords: النظم الاجتماعية -- الزواج المبكر -- طلاب المدارس -- التحصيل الدراسى -- الريف المصرى